Kiai dan Pengembangan Nilai-nilai Multicultural di Pondok Pesantren Amanatul Ummah, Pacet Mojokerto ABST - Tri Wahyudi Ramdhan; Saifuddin Saifuddin; Noah Salomon; Junaidi Junaidi; Bustomi Arisandi (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2022)
Multiculturalism is highly relevant to Islam. Multicultural values go alongside Islamic values. The implementation and practice of multiculturalism in Islamic education has been running in the natural life of the pesantren community. However, multiculturalism in pesantren cannot be separated from the participation of a kiai as the highest leader. This paper reveals the multicultural values found in the natural life of the pesantren community; when the students study, in the dormitory, the Koran, when they eat, pray, read wirid and so on. In addition, this paper reveals the existence of a kiai figure who is the actor behind the development of multicultural values. Multicultural values are revealed by examining the daily life of students, which in the grounding of multicultural values runs naturally. Behind all that, there are patterns or models developed by the kiai, namely; building multicultural communities — avoiding sectarian conflicts — fostering moderate Islam and countering radical ideologies.